Hazardous and contaminated sites within salt marsh migration corridors in Rhode Island, USA - Burman, Erin; Mulvaney, Kate; Merrill, Nathaniel; Bradley, Michael; Wigand, Cathleen (Journal of environmental management, 2023)
As salt marshes attempt to migrate upland due to sea level rise, they will encounter many kinds of land development and infrastructure in highly populated, urbanized coastal communities. Hazardous and contaminated sites (HCSs) -- facilities and infrastructure that store, use, or release harmful substances -- are particularly concerning obstacles to salt marsh migration because of their potential to release contaminants if their structural integrity is compromised. Inventorying HCSs within migration pathways can inform coastal resilience planning. To understand what kinds of HCSs migrating marsh may encounter in Rhode Island, USA, we inventoried sites from federal and state sources, assigned contaminant hazard rankings to most sites, and overlayed them with projected marsh migration corridors. We found that HCSs are extensive across marsh migration corridors in the state, especially in urban areas. Among the most common HCSs in and around Rhode Island salt marshes are stormwater outfalls, underground storage tanks, and facilities registered with EPA's Resource Conservation and Recovery Act (RCRA) or EPA's National Pollutant Discharge Elimination System (NPDES). These sites pose varying hazards to human and aquatic life if breached, with some sites representing little or no threat but most posing some degree of hazard to their surroundings. This coastal HCSs inventory can inform prioritization and management of coastal salt marshes subject to accelerated sea level rise. Management decisions such as allowing marsh migration, implementing adaptation actions to build salt marsh elevation, or erecting physical barriers at marsh sites will influence future salt marsh extent, marshes' ability to provide ecosystem services, and public health exposures to toxic releases. In addition, as Rhode Island and other coastal states work to promote coastal resiliency, this type of inventory can inform decisions about which HCSs to prioritize for remediation and other climate adaptation actions. Marsh migration is just one potential consequence of sea level rise, so many of the considerations outlined here are widely applicable to the broader goal of preparing coastal communities for rising seas. [Display omitted] •Many hazardous and contaminated sites are in Rhode Island marsh migration corridors.•These sites contain, handle, or discharge hazardous substances.•If inundated, sites pose varying hazards to waterways and surrounding communities.•Overlap is opportunity for collaboration among coastal resilience planners.